MICROBIAL ANALYSIS IN NEYVELI LIGNITE CORPORATION LIMITED ENVIRONMENT TAMILNADU, INDIA - C.CHELLARAM; S.VENKATESH; T. PREM ANAND; C.FELICIA SHANTHINI (International Journal of Pharma and Bio Sciences, 2013)
The study was carried out in the field of Aerobiology, Which deals with Microorganism, pollen grains, dust practices and other biological systems in air. This study was conducted to monitor the microbial population present in Neyveli Lignite Corporation Limited (NLC) Environment. The samples were collected on Indoor and outdoor Locations of Neyveli to measure the microbial load like, Bacteria, Fungi and actinomycetes. The Sample was collected using Hipetri Air Sampling system, with different medium and incubation combinations for the capture and identification of Bacteria and fungi. The Results of the study showed that Bacterial and fungal counts measured inside and outside the Environments of NLC, are within the permissible level. Bacteria belonging to the genus Staphylococcus, Streptococcus, Bacillus, and Pseudomonas were most commonly identified in the Air samples from both inside and outside the NLC Environment. Fungi Colonies Predominated by the Genus Aspergillus in the nearby environment. The NLC Environment is safe based on OSHA Standards and it provides safety for its workers.